Contribution to the knowledge of Cladocera (Crustacea: Branchiopoda) from Costa Rica - Avilés-Vargas, Lidia; Rocha Sousa, Francisco Diogo; Umaña-Villalobos, Gerardo (Revista de Biología Tropical, 2025)
Introduction: The topography of Costa Rica varies dramatically, from coastal lowlands to high mountain ranges and volcanoes up to 3 800 m.a.s.l.. In this landscape, lakes and wetlands are observed, harboring diverse crustacean fauna that is not yet thoroughly known. Freshwater fauna in Costa Rica has not been reviewed since the 1980s, but some species not previously reported in the literature have recently been found during limnological studies in the country. Objective: A study of Cladocera was performed to increase the knowledge of this group in Costa Rica. Methods: Sampling was carried out in small ponds and along lake shores, especially among the aquatic vegetation, which has not been included in regular limnological surveys. Samples were screened to extract all members of Cladocera, and these were identified according to the most recent taxonomic literature. Limnological literature on Costa Rican lakes was also examined to complement the list of species. Results: A total of 26 taxa of Cladocera were identified, of which 15 are new reports in Costa Rica, and the total number of Cladocera species for the country has increased to 54. New records for Costa Rica are: Acantholeberis curvirostris, Acroperus tupinamba, Biapertura ossiani, Alonella dadayi, Anthalona verrucosa, Camptocercus dadayi, Chydorus dentifer, Chydorus sphaericus, Ephemeroporus tridentatus, Flavalona iheringula, Parvalona parva, Simocephalus mirabilis, Daphnia ambigua, Leydigia striata and Diaphananosoma brevireme. These include four species reported for the first time in Central America, including A. curvirostirs found in high-altitude bogs. Chydoridae was the most diverse family. Most species were found only at one site, and in very low abundances. Conclusions: It was not possible to identify a few of the specimens, which suggests that the real diversity of Cladocera in Costa Rica is higher, and there might be some species yet to be formally described.